Nitrogen remobilization and its importance in nitrogen use efficiency (NUE) of crops - PADHAN, BIRENDRA KUMAR; SATHEE, LEKSHMY; JAIN, VANITA (The Indian Journal of Agricultural Sciences, 2021)
Nitrogen (N) remobilization during grain filling from pre-anthesis N uptake and stored in different tissues of crop N use efficiency (NUE). N is remobilized from to sink (young leaves or grains) with the help of nitrate/amino acid transporters. Nearly 80% of grain N in cereals is derived from N remobilized from vegetative tissues. Remobilization of N within the plant takes place from older leaves to young leaves, leaves to grains, senescing organs to grains, from storage parts to grains. Enzymes involved in N remobilization include glutamine synthetase (GS), glutamate dehydrogenase (GDH), asparagine synthetase (AS) and proteases. Among them, cytosolic GS plays a key role during N remobilization in cereals. There are various senescence-associated genes (SAG) involved in N remobilization from older degrading leaves to younger leaves and grains. Autophagy (ATG) is an important mechanism involved in the degradation of stored N in the form of various proteins to amino acids, which are transported to long-distance in the form of glutamine and asparagine via phloem tissue. There is a complex network of genes, mechanisms, and factors associated with N remobilization, which needs to be considered for improving NUE of crops.